2012
DOI: 10.1016/j.cell.2011.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Base-Resolution Analyses of Sequence and Parent-of-Origin Dependent DNA Methylation in the Mouse Genome

Abstract: Summary Differential methylation of the two parental genomes in placental mammals is essential for genomic imprinting and embryogenesis. To systematically study this epigenetic process, we have generated a base-resolution, allele specific DNA methylation (ASM) map in the mouse genome. We find parent-of-origin dependent (imprinted) ASM at 1,952 CG dinucleotides. These imprinted CGs form 55 discrete clusters including virtually all known germline differentially methylated regions (DMRs) and 24 previously unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

47
492
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 496 publications
(541 citation statements)
references
References 75 publications
47
492
0
2
Order By: Relevance
“…15). These studies indicate that the mCG landscape is generally similar in postnatal neurons and other cell types, so that intergenic regions and repeat DNA contain high levels of mCG, and active regulatory elements (e.g., enhancers and promoters depletion) are depleted of mCG (8,9,(16)(17)(18). Thus, in neurons, as in other cell types, mCG is thought to silence the transcription of repeats across the genome and to regulate gene expression by promoting transcriptional repression (19,20).…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…15). These studies indicate that the mCG landscape is generally similar in postnatal neurons and other cell types, so that intergenic regions and repeat DNA contain high levels of mCG, and active regulatory elements (e.g., enhancers and promoters depletion) are depleted of mCG (8,9,(16)(17)(18). Thus, in neurons, as in other cell types, mCG is thought to silence the transcription of repeats across the genome and to regulate gene expression by promoting transcriptional repression (19,20).…”
mentioning
confidence: 95%
“…Here, the results of base-resolution methylation mapping from the brain provide a clue to explain these apparently incongruous findings. These recent methylome analyses report that strong bias for mCH occurs in the CA context [∼60% of mCH appears as CA methylation (mCA)], with several studies identifying a longer preferred sequence than just mCA (8,9,17). In this regard, the oligonucleotide probe used in the recent study by Guo et al (9) included mCH with the preferred sequence context, suggesting that MeCP2 binding to mCH might display sequence preferences.…”
Section: Binding Of Mecp2 To the Brain-specific Methylomementioning
confidence: 99%
See 2 more Smart Citations
“…For instance, non-CpG methylation is particularly abundant in mouse and human brain tissue. 17,18 Analysis of human adult brain tissue (specifically the dorsolateral prefrontal cortex of healthy donors) showed that 666/2466 non-CpG dinucleotides tested across the genome were methylated across all 24 individuals tested. 18 An interesting characteristic of non-CpG methylation is that it can occur in a variety of sequence contexts, but is most frequently found at CpA dinucleotides.…”
Section: Evidence For Non-cpg Methylation In Mammalian Cellsmentioning
confidence: 99%